PERLAWANAN RAKYAT PROBOLINGGO DALAM MENUMPAS AGRESI MILITER BELANDA 1947-1949 - Umi Hani Novianti (Historiography: Journal of Indonesian History and Education, 2021)
The history of Indonesian independence cannot be separated from the role of society in gaining independence from colonialists. The Indonesian independence that was achieved was full of twists and turns. After independence was achieved and proclaimed on August 17, 1945, Indonesia was not fully independent because in the early days of Dutch independence returned to Indonesia to occupy Indonesia again. The arrival of the Dutch was opposed by the Indonesian people who had ingrained them in their minds that they were already independent and no longer had to be under the shadow of the Dutch. Finally, conflicts with the Netherlands erupted in several areas. The conflict was an effort to defend Indonesia's independence. One of the conflicts that occurred was in the Probolinggo area. In this conflict the role of youth in defending independence was very important. Youth in Probolinggo moved guerrillaly to fight against the Dutch. The famous figure behind the peoples guerrilla movement against the Dutch in Probolinggo namely is Dr. Moehammad Saleh, he is a doctor and part of the organization founded by Soetomo, namely Boedi Oetomo. Probolinggo guerrillas jointly resisted Dutch military aggression with thw help of important figures in it.Sejarah kemerdekaan Indonesia tidak terlepas dari peranan masyarakat untuk meraih kemerdekaan daripenjajah. Kemerdekaan Indonesia yang diraih penuh dengan lika-liku dan pengorbanan. Setelah kemerdekaan dapat diraih dan dikumandangkan pada tanggal 17 Agustus 1945, Indonesia belum sepenuhnya benar-benar merdeka karena pada masa awal kemerdekaan Belanda kembali ke Indonesia untuk menduduki Indonesia lagi. Kedatangan Belanda ini ditentang oleh masyarakat Indonesia yang sudah tertanam dibenak mereka bahwa, mereka sudah merdeka dan tidak lagi harus dibawah bayang-bayang Belanda. Akhirnya di beberapa daerah meletus konflik dengan Belanda. Konflik tersebut sebagai upaya mempertahankan kemerdekaan Indonesia. Salah satu konflik yang terjadi yaitu di daerah Probolinggo. Dalam konflik tersebut peranan dari rakyat untuk mempertahankan kemerdekaan sangat penting. Rakyat di Probolinggo bergerak secara gerilya untuk melawan Belanda. Tokoh yang terkenal dibalik pergerakan rakyat secara bergerilya melawan agresi militer Belanda di Probolinggo yaitu Dr. Moehammad Saleh, dia adalah seorang dokter sekaligus tergabung dalam organisasi yang didirikan oleh Soetomo yaitu Boedi Oetomo. Para gerilyawan Probolinggo secara bersama melawan agresi militer Belanda dengan bantuan tokoh-tokoh penting didalamnya.